Cryptocurrencies in Nigeria - Izevbigie, Iyen Don-Pedro; Alegbe, Alegbe (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The objective of this paper is to theoretically examine the place of the use of cryptocurrencies in entrepreneurship, accounting and taxation in Nigeria. Design/methodology/approach: The methodology used is library-based research through review of related extant literature which informed the position taken in this paper. From the critical review of literature, it can be inferred that despite the novelty and attraction these digital currencies promise, it is not without inherent limitations, but requires the needed legal and regulatory framework in order for it to enhance security of the value of money of the owners who may want to key into it usage. Findings: It is therefore recommended that the relevant national and international money market/financial regulators and authorities should take proactive steps in coming up with the needed framework to help eliminate any doubt that may be associated with the use of cryptocurrencies. Paper type: Research Paper.